Machismo and violence against women - Oblitas Béjar, Beatriz (2009)
Study allows conclusion that there is a double discourse, that of reality and that of desire. The one of reality makes recognition to what it is to be man and woman within the patriarchal system, stemming from machismo guidelines that society assigns. Women are still locating in the private/domestic field, being responsible for provision of love and care to children. The discourse of desire that poses as real, points what is ideal for the man-woman relationship. When the responses of this speech are compared to the other, is when they appear as aspiration. That is the case of views concerning the work of men in kindergartens, to the crying of men, infidelity, violence between the couple, or when men do not consider themselves «macho men». Violence against women is closely associated with the patriarchal system or macho system, as it is called colloquially. This system justifies, plays and tolerates a series of imaginary and practices among men and women, which on the basis of inequality and gender discrimination, ends up affecting the family life.